Assessing the risk exposure in IT outsourcing for large companies. (6th June 2011) - Rusu, Lazar; Hodosi, Georg
The decision process for companies to outsource information technology (IT) or not is a substantial business change and in many cases the competence to take such decisions is limited and has major consequences for the company's future performance. In this context, the paper is presenting the design of an information technology outsourcing (ITO) tool that includes a procedure based on transaction cost theory (TCT) for assessing the risk exposure in ITO. The ITO tool presented in this paper is a useful and effective instrument for the IT decision-makers in support of decisions to outsource IT or not. In the development of the ITO tool, we have approached two large companies in Sweden with more than 20 years experiences in ITO that helped us in the improvement and evaluation of the usability and effectiveness of this tool.